Novel Pharmaceutical Strategies for Enhancing Skin Penetration of Biomacromolecules - Luyu Zhang; Zirong Dong; Wenjuan Liu; Xiying Wu; Haisheng He; Yi Lu; Wei Wu; Jianping Qi (MDPI AG, 2022)
Skin delivery of biomacromolecules holds great advantages in the systemic and local treatment of multiple diseases. However, the densely packed stratum corneum and the tight junctions between keratinocytes stand as formidable skin barriers against the penetration of most drug molecules. The large molecular weight, high hydrophilicity, and lability nature of biomacromolecules pose further challenges to their skin penetration. Recently, novel penetration enhancers, nano vesicles, and microneedles have emerged as efficient strategies to deliver biomacromolecules deep into the skin to exert their therapeutic action. This paper reviews the potential application and mechanisms of novel skin delivery strategies with emphasis on the pharmaceutical formulations.